UPAYA KEPOLISIAN DALAM PENANGANAN TERHADAP PELAKU TINDAK PIDANA TERORISME - Ester Balebu; Suzanna Lumeno (UNES Law Review, 2022)
The number of acts of terror that have occurred in Indonesia has forced the Indonesian government to always make efforts to prevent and control various acts of terrorism that have occurred. Considering that in carrying out their actions terrorist groups always use weapons and bombs, a strategy is needed to prevent terrorism crimes. The research method used in this study is the Normative Legal Research Method. In this study, 2 (two) approaches were used, namely: Statute approach and conceptual approach. To take a stance on various types of terrorist attack incidents that create fear in the Indonesian people, the government has taken strategic steps in tackling criminal acts of terrorism, including by issuing a Government Regulation in Lieu of Law on the Eradication of Criminal Acts of Terrorism, and a year later a Perpu In 2002 this was confirmed as a regulation regarding the Suppression of Terrorism Delicts. Based on various considerations, it is necessary to regulate the Regulation of the Head of the National Police of the Republic of Indonesia Number 23 of 2011 concerning Procedures for Enforcement of Terrorism Suspects. The stages that must be passed to take action against criminal acts of terrorism are (1) carrying out an agreement (2) carrying out a warning (3) carrying out infiltration (4) thwarting levies (5) carrying out arrests (6) carrying out searches (7) carrying out confiscation of evidence.